PHYSICAL, CHEMICAL, AND ORGANOLEPTIC CHARACTERISTICS OF RICE ANALOG MADE FROM MOCAF, CORN FLOUR (Zea mays L.), AND MUNG BEAN SPROUT FLOUR (Vigna radiata L.) - Yulviatun, Anastriyani; Purnamasari, Suci; Ariyantoro, Achmad Ridwan; Atmaka, Windi (Universitas Sebelas Maret (UNS), 2022)
The food intake of Indonesian people includes a typically high amount of rice. However, the domestic production of rice has not fulfilled the needs. Therefore, a rice analog whose characteristics resemble rice could be an alternative rice substitute. The rice analog discussed in this study was made from a combination of mocaf, cornflour, and mung bean sprout flour. The study aimed to discover the effect of different combinations of the three main ingredients on rice analog's chemical and physical characteristics, to obtain the best formulation based on sensory evaluation, and to evaluate its chemical and physical properties.This study began with the manufacture of mung bean sprout flour and then the manufacture of rice analog. This study was conducted by completely randomized design (CRD) with a ratio between mocaf and mung bean sprout flour as the single factor. The 5 formulas to be assessed were F1 (50%:10%), F2 (40%:20%), F3 (30%:30%), F4 (20%:40%), F5 (10%:50%). A sensory evaluation was conducted by the hedonic test scoring method.Based on sensory evaluation, formula F1 that was composed of 50% mocaf, 40% corn flour, and 10% mung bean sprout flour was the best formulation among all. This formula had a yellowish-white color, hulled rice-like oval and long shape, insipidity, neutral flavor, and sticky texture. The rice analogue F1’s chemical characteristics included 7.301% water content (wb), 1.284% ash content (db), 6.513% fat content (db), 6.694% protein content (db), 75.198% carbohydrate content (db), 23.365% amylose content, and 13.164% antioxidant content. Based on physical analysis, this rice analog had color value 76.208 °Hue (yellow-red colors), weight per grain 0.027g, bulk density 0.556 g/ml, water absorption 118%, cooking time 7.222 minutes, and swelling power 27.254%.